Women's colleges and economics major choice: Evidence from Wellesley College applicants - Kristin F. Butcher; Patrick J. McEwan; Akila Weerapana (Federal Reserve Bank of Chicago, 2023)
Many observers argue that diversity in Economics and STEM fields is critical, not simply because of egalitarian goals, but because who is in a field may shape what is studied by it. If increasing the rate of majoring in mathematically-intensive fields among women is a worthy goal, then understanding whether women's colleges causally affect that choice is important. Among all admitted applicants to Wellesley College, enrollees are 7.2 percentage points (94%) more likely to receive an Economics degree than non-enrollees (a plausible lower bound given negative selection into enrollment on math skills and major preferences). Overall, 3.2 percentage points - or 44% of the difference between enrollees and non-enrollees - is explained by college exposure to female instructors and students, consistent with a wider role for women's colleges in increasing female participation in Economics.
Keywords: 330; Frauen; Hochschule; Studierende; Studium; Berufswahl; Bildungsverhalten; Wirtschaftswissenschaft